2017
DOI: 10.1101/224881
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A suite of transgenic driver and reporter mouse lines with enhanced brain cell type targeting and functionality

Abstract: SUMMARYModern genetic approaches are powerful in providing access to diverse types of neurons within the mammalian brain and greatly facilitating the study of their function. We here report a large set of driver and reporter transgenic mouse lines, including 23 new driver lines targeting a variety of cortical and subcortical cell populations and 26 new reporter lines expressing an array of molecular tools. In particular, we describe the TIGRE2.0 transgenic platform and introduce Cre-dependent reporter lines th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(98 citation statements)
references
References 68 publications
(94 reference statements)
1
97
0
Order By: Relevance
“…Foxp2-ires-Cre (Jax 030541), Nkx2.1-ires-Flp (Jax 028577), Npas1-Cre-tdTomato BAC (Jax 027718), PV-ires-Cre (Jax 017320), PV-2A-Flp (Jax 022730), PV-tdTomato BAC (Jax 027395). FSF-tdTomato (Ai65F) was generated as previously described (Daigle et al, 2018;Yetman et al, 2019). In brief, FSF-LSL-40 tdTomato was crossed with EIIa-Cre (Jax 003724) to delete the LSL cassette.…”
Section: Micementioning
confidence: 99%
“…Foxp2-ires-Cre (Jax 030541), Nkx2.1-ires-Flp (Jax 028577), Npas1-Cre-tdTomato BAC (Jax 027718), PV-ires-Cre (Jax 017320), PV-2A-Flp (Jax 022730), PV-tdTomato BAC (Jax 027395). FSF-tdTomato (Ai65F) was generated as previously described (Daigle et al, 2018;Yetman et al, 2019). In brief, FSF-LSL-40 tdTomato was crossed with EIIa-Cre (Jax 003724) to delete the LSL cassette.…”
Section: Micementioning
confidence: 99%
“…Because steroid hormone receptors are expressed only in a subpopulation of cells within sexually dimorphic brain regions, it is critical to isolate specific cell types prior to downstream genomics assays. Cell-type targeting has been made possible with Cre-loxP and Flp-FRT recombination systems, which rely on cell-type-specific active gene promoters to facilitate knockin-knockout expression of fluorescent reporter or molecular-tagging alleles (Daigle et al, 2018;Tsien et al, 1996). When Cre and Flp animals are crossed, cells co-expressing two driver genes may be labeled, allowing for more refined targeting .…”
Section: Gonadal Steroid Hormones Direct Sexual Differentiation Of mentioning
confidence: 99%
“…We found that the percentage of endocardial cells expressing tdTomato was significantly higher in Npr3-sCreER;R26-LZLT than Npr3-CreER;R26-LZLT ( Fig 3C-E). Additionally, we crossed Npr3-sCreER or Npr3-CreER with R26-GFP reporter (Daigle et al, 2018;Zhao et al, 2018) and found that Npr3-sCreER was far more efficient in recombining R26-GFP than Npr3-CreER (Appendix Fig S6). Taken together, the above data demonstrated that sCreER was more efficient than CreER in recombination of a refractory target locus.…”
Section: Of 12mentioning
confidence: 99%